2016
DOI: 10.1063/1.4972868
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gold nanoparticles on lipid packing and membrane pore formation

Abstract: Gold nanoparticles (AuNPs) have been increasingly integrated in biological systems, making it imperative to understand their interactions with cell membranes, the first barriers to be crossed to enter cells. Herein, liposomes composed of 1,2-dimyristoyl-sn-glycero-3-phosphocholine (DMPC) as a model membrane system were treated with citrate stabilized AuNPs from 5 to 30 nm at various concentrations. The fluorescence shifts of Laurdan probes reveal that AuNPs in general made liposomes more fluidic. The increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…Therefore, we hypothesize that the ability of cations to disrupt the outer layer of lipid membranes occurs at a much greater extent for AuNPs than for AgNPs. Numerous experimental and simulation studies have reported the disruption of lipid bilayers by AuNPs [ 27 , 31 , 32 , 33 , 34 ]. In the mean while when the AuNPs disrupt the outer leaflet of the lipid bilayer, the citrate anions are likely stripped off and left in the aqueous solution as the hydrophobic force between the acyl chains of DMPC and AuNPs outweighs the solvation force.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, we hypothesize that the ability of cations to disrupt the outer layer of lipid membranes occurs at a much greater extent for AuNPs than for AgNPs. Numerous experimental and simulation studies have reported the disruption of lipid bilayers by AuNPs [ 27 , 31 , 32 , 33 , 34 ]. In the mean while when the AuNPs disrupt the outer leaflet of the lipid bilayer, the citrate anions are likely stripped off and left in the aqueous solution as the hydrophobic force between the acyl chains of DMPC and AuNPs outweighs the solvation force.…”
Section: Discussionmentioning
confidence: 99%
“…The AgNPs (10 nm, 0.02 mg/mL, Sigma-Aldrich #730785) used in this work were prepared by the reduction of silver nitrate and citrate-stabilized in aqueous buffer [ 39 ]. The size of 10 nm was chosen in this study because our earlier work showed that 10-nm AuNPs were most effective in inducing the phase and shape changes in lipid vesicles [ 27 ]. The TEM images of AuNPs and AgNPs ( Figures S1a and S2 ) used in this study and more details on size distribution ( Figure S1b ), concentration and citrate stabilization ( Figure S3 ) can be found in the Supplementary Material .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This process has been achieved through the electrostatic interactions that occur between oppositely charged lipid bilayers and NPs as well as through the direct synthesis of NPs on the bilayer surface . The adsorption of charged NPs on the outer surface of liposomes provides an additional benefit of increasing liposomal stability due to electrostatic repulsions between NP‐decorated liposomes of the same charge, which prevents liposomal fusion . Phosphatidylcholines, which possess a zwitterionic headgroup containing a negatively charged phosphate and a positively charged choline, are the most commonly used lipids used to form liposomes.…”
Section: Methods and Effects Of Incorporating Inorganic Nps Into Drugmentioning
confidence: 99%
“…[42][43][44][45] The adsorption of charged NPs on the outer surface of liposomes provides an additional benefit of increasing liposomal stability due to electrostatic repulsions between NP-decorated liposomes of the same charge, which prevents liposomal fusion. [46][47][48][49] Phosphatidylcholines, which possess a zwitterionic headgroup containing a negatively charged phosphate and a positively charged choline, are the most commonly used lipids used to form liposomes. Despite the net neutrality of the headgroup, there is a dipole, allowing the electrostatic attraction of charged nanoparticles.…”
Section: Nps Adsorbed Onto the Liposome Bilayersmentioning
confidence: 99%